Toulmin Argument Patterns in Asian EFL Learners’ Essays: Gender and Topic-Based Comparison - Indarti, Dwi (JOLLT Journal of Languages and Language Teaching, 2025)
This study explores Toulmin Argument Patterns (TAP) in argumentative essays by Asian EFL learners, focusing on gender and topic-based comparison. Using an adapted Toulmin model, it analyses argument components, claims, data, counter-arguments, and rebuttals, from the ICNALE corpus on topics "smoking" and "part-time job". Indonesian female learners constructed higher-quality arguments with comprehensive rebuttals, whereas their male counterparts relied more on basic elements. Among Chinese learners, gender differences were minimal, with both genders showing balanced TAP use, reflecting structured critical-thinking education. Familiar topics like "part-time job" led to more complex arguments, while less relatable topics like "smoking" resulted in weaker argumentation. Cultural factors also influenced argument quality, with Confucian-influenced education fostering consistency among Chinese learners and diverse educational practices leading to variability in Indonesian learners. These insights can inform curriculum design by encouraging the integration of culturally relevant and gender-responsive writing tasks that support students’ critical thinking and argumentative skills. Future research should expand to broader linguistic and cultural contexts to refine TAP-based pedagogical strategies and deepen understanding of argumentative competence in EFL settings.